SECURITY BREACH INCIDENCES OF SACCOS WITH OR WITHOUT SECURITY POLICY WITH A BROAD SCOPE: A CASE OF SACCOS IN KENYA - Sirma, Jerotich; Raburu, George; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
The risks that organizations face include safeguarding information resources in their networks. Organizations have formulated security policies with the hope of solving the problem of security breaches or to significantly reduce incidences of security breaches. However, systems are still vulnerable to security breaches. The vulnerability may arise from security breaches that could be internal or external to the organization. A security breach can result in the risk of an intrusion into the SACCOS’ sensitive information. For example, an intruder can potentially gain access to SACCOS client documents that may contain propriety financial information. Disclosure of client information can result in the loss of confidence in SACCOS and real financial loss. Despite the identification of good security policies and frameworks for security governance in the information systems field, there is still lack of understanding by users about how security breach incidents have the potential to weaken the implementation of security policies in the SACCOS sector. The study will try to fill in the gap upon reporting the results of the study that sought to analyze the relationship between information security policies and the incidences of security breaches in the SACCOS sector in Kenya.